CONSUMER BEHAVIOR AS THE BASIS OF MERCHANDISE - HROMOVA, Olha; ABDULLAIEVA, Anastasiia; SHEVCHUK, Anna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The effective operation of any company in the market is necessarily related to the analysis of consumer behavior. At the time of constant transformational changes in society, unpredictable risks that arise in the country, the question of understanding the theory of consumer behavior and the possibility of influencing it with the help of available resources is relevant.The purpose of the article is to reveal the essence of the concept of consumer behavior and the main elements that influence the customer's choice, as well as how to correct behavior and minimize losses during a crisis and martial law. The development of society inevitably affects consumers, their needs are transformed, improved, and costs to satisfy these needs increase. Therefore, consumer behavior is changing and companies need to adapt to new conditions. The process of making purchase decisions, as a rule, takes place under the influence of various factors. This makes appropriate adjustments, facilitates or hinders the adoption of balanced decisions. The main factors that influence purchase decisions.The latest challenge was the coronavirus pandemic, which also affected consumer behavior and made quite a few adjustments. Due to the threat to health and the imposed restrictions, people's habits, the frequency and places of purchases, the structure and volumes of consumption, the needs of the population and, in general, the behavior of consumers have changed. Now, not only merchandising, but the functioning of the country's economy in general, satisfaction of consumer needs during the war is an urgent issue. Since the market was quite complicated by the consequences of the pandemic, consumer behavior was strongly influenced by military actions.It is worth noting that even during the war, Ukrainian companies show a high level of customer service that even some European companies cannot provide. Most from the very beginning of the full-scale invasion restored customer support, and later returned, and some even introduced discount systems and personal bonus systems. Government policy was also aimed at supporting users, interest charges, fines and penalties were abolished, which enabled the population to withstand the period of economic shock.In the period of such unpredictable global changes, increased risks, consumer behavior undergoes a noticeable transformation. However, companies constantly monitor the situation and show that they are well aware of the needs of their customers and can adapt to modern trends, thereby supporting the economy of the country and their consumers.
Keywords: consumer behavior; assortment; product; service; merchandising